2011
DOI: 10.1097/inf.0b013e3181f7ce44
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Influenza Vaccine in Children With Pediatric Rheumatic Diseases Receiving Immunosuppressive Agents

Abstract: In the children with pediatric rheumatic diseases receiving immunosuppressive agents, influenza vaccination resulted in serum antibody titers similar to those in the controls without major adverse effects. Such children receiving immunosuppressive therapy are a high-risk group for influenza virus infection, therefore vaccine should be given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 15 publications
(16 reference statements)
3
53
2
4
Order By: Relevance
“…This study design provided strong evidence that the immunoresponse to influenza A H1N1/2009 vaccine was impaired in the juvenile ARD population, in contrast to previous studies on seasonal influenza vaccination 6,7,8 . In this regard, Malleson, et al evaluated 34 children with chronic arthritis (91% JIA) and observed similar seasonal vaccine immunogenicity in patients and 13 controls, independent of the use of prednisone or immunosuppressive agents 7 .…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…This study design provided strong evidence that the immunoresponse to influenza A H1N1/2009 vaccine was impaired in the juvenile ARD population, in contrast to previous studies on seasonal influenza vaccination 6,7,8 . In this regard, Malleson, et al evaluated 34 children with chronic arthritis (91% JIA) and observed similar seasonal vaccine immunogenicity in patients and 13 controls, independent of the use of prednisone or immunosuppressive agents 7 .…”
Section: Discussioncontrasting
confidence: 45%
“…The preimmunization rate cannot account for this finding because it was similar to that of the control group. In contrast, previous reports suggest apparently adequate vaccine responses for seasonal influenza 8 and hepatitis 27 in persons with JIA. The inclusion of patients or controls younger than age 9 years 8,27 and 3 years old 8 precludes a definitive conclusion about their findings, as vaccine responses in these 2 age brackets are expected to be much lower than in older children.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations